Ruling of Tawassul in Islam - Khairunnisak, Khairunnisak (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2023)
The difference in the nature and quality of taqwa between one person and another is like a ladder. The higher a person's taqwa, the closer he is to Allah SWT. A person who has committed many sins against his Lord and he wants to ask Allah for his needs, sometimes he feels inappropriate to do so, when in fact it is okay for him to do so. This causes him to look for intermediaries who can help him to pray for him. Asking for help like this is what is called tawassul. Thus this paper wants to examine the main issue, namely: What are the proofs and arguments about tawassul?. This writing uses qualitative research methods. This type of research is only in the form of words, in which case the author does not use data in the form of numbers directly. Then proceed with the data collection method that the author uses the library research method, which means that the author collects data by reading books, journals, or other forms of scientific work. The result of this writing is that tawassul with the asma of Allah SWT, with the Prophet SAW, with the Wali Allah and with our good deeds and good deeds is allowed based on the arguments that the author has described above. So far, the scholars who allow tawassul and do it do not have the slightest belief that they (who are used as intermediaries) are the ones who grant requests or who give harm. They believe that it is Allah who has the right to grant and reject the prayers of His servants.